PENGARUH PERTUMBUHAN INVESTASI MODAL MANUSIA DAN MODAL FISIK TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Kliwan Kliwan (Jurnal Ekonomi Pembangunan, 2006)
The objective of this research are to analize the influence of physical capital and human capital on the economic growth of  Indonesia. The data processed and analyzed were secondary data consisted of time series data during the period of 1990 – 2004 gathered from Statistics of Indonesia collected by the Statistic Centre Institution (BPS) including output (GDP), physical capital (proxied by gross domestic fixed capital) and human capital (proxied by the number of workers which is grouped by level of formal education). Then regression calculation was done by using the Endogen Economic Growth Model. To know whether it was statistically influential or not, the Classic Asumption test and Statistics test were done by using the assistance of SPSS computer program. From the results of this research, it can be concluded that : Although the 3rd Level Effective Labor (Labor with Academy or University education level) (Ln Pkj E3)  variable has the most little elasticity coefficient (0,289),  it really has a positive and most significant influence to the economic growth in Indonesia than the elasticity coefficient of 2nd Effective Labor (0,437) and 1st Effective Labor (-1,796). The Annual Gross Domestic Fixed Capital (Ln Mt)  variable elasticity coefficient is  0,381 and it has a positive and significant influence too, but the Gross Domestic Fixed Capital A Year Ago variable is not. The result of Adjusted R2 value is 0,955, which is means 95,5% of  the variation of tied variable (Economic Growth in Indonesia) in the model mentioned above are able to explain by the variation of, while the rest  of  free variable used (3rd Level Effective Labor and Gross Domestic Fixed Capital) while the 0,05% residual variation are explained by another variables which are not used in this research model.   Keywords: physical capital, human capital, economic growth